Emotional intelligence and management of school culture in Nigeria - Enefiok, Ukpabio, Godfrey; Ekpenyong, Ekanem, Ekpenyong; Iyaji, Ngaji Mary; Eja, Ojong, Felix; Nkemdilim, Amalu, Melvina (Nurture, 2023)
Purpose: The purpose of this study was to examine the concept of Emotional Intelligence (EI) and determine if managers’ emotional intelligence is a significant predictor of school culture. It also examined the possibility that gender may have an effect on managers’ influence on school culture. Design/Methodology/Approach: The study used a survey research method in order to learn more about how managers’ emotional intelligence (EI) affected school culture in the study region during the time of the research. The independent t-test and multiple regression analysis were used to analyse the data using a sample of 100 vice principals. Findings: The findings indicated that managers’ emotional intelligence influence on school culture varies by gender and that the emotional intelligence of school managers is a significant predictor of school culture. Conclusion: According to the results’ interpretation, emotionally intelligent principals can improve the school’s environment making it more friendly and compassionate. Principal plays a significant role in their management effect on school culture. Research Limitations and Practical Implications: Stakeholders can practically create a positive school culture and rid the school system of a toxic atmosphere by improving their employees’ EI competencies which are important comprehensible skills. Future research should aim at finding out specific areas of differences between male and female managers’ EI. Contribution to the Literature: The results of this study may serve as a tool for policymakers in teacher and student personnel management, in addition to providing literature for future research. It may also serve as a resource for school improvement.